Civil Religion in African-American Mourning Songs about John F. Kennedy - Wester, Anne (Student Undergraduate Research E-journal!, 2016)
This research focuses on a selection of African-American songs about the death of John F. Kennedy. The paper thereby particularly concentrates on the question how African-American artists express civil religious ideas in relation to the efforts and accomplishments of the Kennedy Administration, the comparisons that are made between Biblical figures and the slain president, and the manner in which these artists express civil religion when discussing the future of the United States after the death of the President. It thereby not only zooms in on the African- American musical and cultural heritage, but also on the role of Christianity in 1960s America.